Determination of phenolics and saponins in fenugreek seed extracted via microwave-assisted extraction method at the optimal condition - S., Akbari; A. H., Nour; R. M., Yunus (Institute of Physics Publishing, 2020)
Fenugreek an ancient plant also known as Trigonella-foenum-graecum L. This plant has achieved a great interest due to its valuable medicinal properties. The current research is targeted to extract phenolic and saponin bioactive compounds from seeds of fenugreek via microwave-assisted extraction (MAE) technique. The seed extraction was carried out at irradiation time of (2-4 min), microwave oven power (500-700 W), ethanol concentration (4080 %), ratio of seed-to-extraction solvent (1:8-1:12 g/mL) and a constant extraction temperature (70°C). The statistical process of response surface methodology (RSM) under software of Design-Expert was used to optimize the recovery of total saponin content (TSC) and total phenolic content (TPC) in extract of fenugreek seed. One-factor-at-one-time (OFAT) was used to evaluate the levels of independent factors, and the suitable levels (-1, 0, and +1) were selected for the optimization process. Results indicated that the optimal conditions of extraction process to achieve the highest recoveries were 2.84 min, 572.50 W, 63.68% and 1:9 g/mL, respectively. Analysis of variance (ANOVA) indicated that TSC and TPC were significantly influenced by the time of irradiation, microwave oven power, solvent concentration, and ratio of seed-to-extraction solvent. FTIR results confirmed the presence of specific peaks belonging to saponins and phenolic compounds.